Green energy potential of rice husk, oil palm wastes and pineapple wastes in Malaysia / George Ong Jun Chong - George Ong , Jun Chong (2017)
This study focused on the green energy potential of selected biomass. Biomass studied were rice husk, rice straw, pineapple solids, empty fruit bunch fibre, mesocarp fibre and kernel shell. Malaysia’s annual production of palm oil has potential of generating 38.18 million metric tons of biomass. Malaysia produced 3.77 million metric tons of biomass of rice husk and rice straw combined. Pineapple as the popular fruit for canning in Malaysia can potentially yield 122, 176 metric ton of biomass. The total biomass in this study was 40.2% of total biomass produced in Malaysia and potentially generate of between 8.9MWh and 10.2MWh of electricity which equates to 1.73% to 2.00% of Malaysia agriculture sector’s electricity consumption annually. Rice husk and straw usage increased maintenance cost due to high ash content. Pineapple and empty fruit bunch contained high moisture content at 88.6% and 62.4% respectively which may require drying as pre-treatment that may incur more energy cost. Palm kernel shell has better potential as fuel source due to its low moisture content and low ash content. Evaluation on potential monetary value was done. First scenario of selling the electricity via Feed-in-Tariff scheme yields a value of RM0.06 to RM0.07 per tonne of biomass. In scenario two, electricity offset using normal industrial tariff yield a value ranging from RM 0.05 to RM0.08 per tonne of biomass. Third scenario is based on current commercial value which yield a value range from RM 20 to RM 150 per tonne of biomass. In summary, all six biomass except rice straw has better monetary value based on commercial value at RM 150 per tonne as raw material for value added products and is most beneficial for the mills and factory owners. However, rice straw has better economical attractiveness when used as a fuel source for electrical energy generation due to its low commercial value.